The Role of a Notary in the Establishment of A Limited Liability Company After the Job Copyright Law Enactment - Destesa Yuna Fahira; Mahmudah, Siti (Department of Law, Universitas Islam Negeri Alauddin Makassar, 2024)
This study aims to analyze the role of notaries in the establishment of limited liability companies after the enactment of Law Number 11 of 2020 regarding job copyright law. This research used normative. The results showed that before the ratification of Law Number 11 of 2020, the establishment of a limited liability company must be done through a notary deed. Article 153A, paragraphs (1) and (2), is a new article in Law Number 40 of 2007 after the enactment of Law Number 11 of 2020. The article specifies that a company that meets the criteria for micro and small enterprises can be established by one person electronically to the Minister based on a statement of establishment. Thus, with these changes, the establishment of an individual company that falls into the category of micro and small enterprises no longer requires a notary deed.